SENI OLAH NAFAS JIAN SHEN QI GONG (Pengamatan Victory Jian Shen Qi Gong Yogyakarta) - , ATHENA DEVINA, Citra Ayu Novitasari, B.Art., M.TCSOL. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final paper entitled Jian Shen Qi Gong Art Of Breathing (Observation Of Yogyakarta Victory Jian Shen Qi Gong) aims to provide an overview of one of the Chinese cultures related to health. The research method that is used in this final paper is a library research, observation, participant, interviews, and questionnaires. Jian Shen Qi Gong is one of traditional sport from China that is well-known since then. Is an effective and efficient sport anyone can do. It is ot limited in the term of place and time. Also, it can strength then oneâs body, cure some illnesses, improve oneâs intelligence and create peace in oneâs mind.